Phototrophic cultivation of NaCl‐tolerant mutant of Spirulina platensis for enhanced C‐phycocyanin production under optimized culture conditions and its dynamic modeling. Issue 1 (15th November 2017) - Gupta, Apurva; Mohan, Devendra; Saxena, Rishi Kumar; Singh, Surendra
Abstract : Commercial cultivation of Spirulina sp. is highly popular due to the presence of high amount of C‐phycocyanin (C‐PC) and other valuable chemicals like carotenoids and γ‐linolenic acid. In this study, the pH and the concentrations of nitrogen and carbon source were manipulated to achieve improved cell growth and C‐PC production in NaCl‐tolerant mutant of Spirulina platensis . In this study,  highest C‐PC (147 mg · L −1 ) and biomass (2.83 g · L −1 ) production was achieved when a NaCl‐tolerant mutant of S. platensis was cultivated in a nitrate and bicarbonate sufficient medium (40 and 60 mM, respectively) at pH 9.0 under phototrophic conditions. Kinetic study of wildtype S. platensis and its NaCl‐tolerant mutant was also done to determine optimum nitrate concentrations for maximum growth and C‐PC production. Kinetic parameter of inhibition (Haldane model) was fitted to the relationship between specific growth rate and substrate concentration obtained from the growth curves. Results showed that the maximum specific growth rate (μmax ) for NaCl‐tolerant mutant increased by 17.94% as compared to its wildtype counterpart, with a slight increase in half‐saturation constant (Ks ), indicating that this strain could grow well at high concentration of NaNO3 . C‐PC production rate (Cmax ) in mutant cells increased by 12.2% at almost half the value of Ks as compared to its wildtype counterpart. Moreover, the inhibition constant (Ki ) value was 207.85% higher in NaCl‐tolerant mutant as compared to its wildtype strain, suggesting its ability to produce C‐PC even at high concentrations of NaNO3 .